Comparison of Laparoscopic and Open Surgery for Women With Early-Stage Epithelial Ovarian Cancer - Ran, Xuting; He, Xinlin; Li, Zhengyu (Frontiers in Oncology, 2022)
Objective This study evaluated the oncologic outcomes of laparoscopy and laparotomy in the management of early-stage ovarian cancer patients. Methods We conducted an observational study of women diagnosed with International Federation of Gynecology and Obstetrics (FIGO) 2014 stage I ovarian cancer who underwent surgery at the West China Second University Hospital from 2012 to 2020. Patients who received adjuvant chemotherapy before surgery, those with non-epithelial histopathological types, or those with insufficient data were excluded. Using propensity score matching, data from consecutive laparoscopic patients treated by laparoscopy were matched 1:2 with a cohort of patients undergoing open surgery. The operative and survival outcomes among the matched cohorts were examined using the Kaplan–Meier method. Results Among 200 eligible patients, 74 patients undergoing laparoscopy were compared with a cohort of 126 patients undergoing open surgery. Baseline characteristics were similar between groups after matching. Patients who had laparoscopy had a shorter operative time (P = 0.001), a shorter hospital stay (P <0.001), and lower blood loss (P = 0.001) than patients who had open surgery. The median (range) follow-up period was 43.0 (38.8–47.2) and 45.0 (36.0–54.0) months for cases and controls, respectively (P <0.001). There are no significant differences in progression-free survival (P = 0.430, log-rank test) and overall survival (P = 0.067, log-rank test) between the two groups. Conclusions There is no difference in prognosis between laparoscopic and open surgery in women with stage I epithelial ovarian cancer. Laparoscopic treatment of early-stage ovarian cancer is safe and feasible for stage I epithelial ovarian cancer patients.